Long-Term Efficacy of Audiologist-Guided Internet-Based Cognitive Behavior Therapy for Tinnitus - Beukes, Eldré W. (Am J Audiol, 2018)
PURPOSE: The purpose of this study was to investigate the long-term outcomes 1 year after undertaking an audiologist-guided Internet-based cognitive behavioral therapy (iCBT) intervention for tinnitus. Secondary aims were to identify any predictors of outcome and whether there were any unwanted events related to undertaking iCBT for tinnitus. METHOD: Participants who had previously undertaken a randomized iCBT efficacy trial for tinnitus were invited to participate. Of the 146 who were initially randomized for the efficacy trial, 104 participants completed the 1-year postintervention assessment measures. The primary outcome was a change in tinnitus distress as assessed by the Tinnitus Functional Index. Secondary assessment measures were included for insomnia, anxiety, depression, hearing handicap, hyperacusis, cognitive failures, and satisfaction with life. An intention-to-treat analysis using repeated-measures analysis of variance and hierarchical multiple regression was used for statistical analysis. Unwanted effects were categorized according to the unwanted events checklist. RESULTS: Undertaking iCBT for tinnitus led to significant improvements 1 year postintervention for tinnitus and related difficulties, for example, insomnia, anxiety, depression, hearing handicap, hyperacusis, and life satisfaction. The best predictors of improving tinnitus severity at 1-year postintervention were greater baseline tinnitus severity scores, reading more of the modules, and higher satisfaction with the intervention. Unwanted events were reported by 11% of the participants and were more likely to be reported by women than men. These events were related to worsening of symptoms, the emergence of new symptoms, negative well-being, and prolongation of treatment. CONCLUSIONS: The clinical benefits of audiologist-guided iCBT for tinnitus and tinnitus-related difficulties were sustained 1 year postintervention. Predictors of outcome indicated that the intervention is applicable to a wide range of participants regardless of their demographic backgrounds. Attempts should be made to minimize unwanted events in subsequent trials.